Indicadores de calidad del suelo en tres zonas de producción del cultivo de cacao (Theobroma cacao L) - Carranza Aguirre, María Belén (2022)
Theobroma cacao L. is one of the agricultural species of great importance at the national level, it represents one of the main export products, being in Ecuador the provinces of Los Ríos and Guayas with the highest production. The main objective of the research was to determine the physical, chemical and biological indicators in the three cocoa (Theobroma cacao L.) producing areas in order to know the quality indicators that were affecting the cocoa soils in the study locations (El Empalme, Mocache and Quevedo).